Respuesta :

This inequality can be transformed into:

(x-7)(x+5) > 0

So the threshold points are x= 7 and x = -5

Then you can find that: when x > 7 and x < -5, this inequality works

So the solution is (-∞, -5) ∪ (7, ∞)
This is not easy ...

First you have to write it as an equation = 0:


x^2-2x-35 = 0.

Then, find the roots with he quadratic formula:

x = (2 +/- sqrt(4 + 280))/2, sqrt(284) = 16.85 ...

Uh, so now with roots:

sqrt(284) = sqrt( 4*71) = 2*sqrt(71), sounds too difficult for an online question ...

Let's move on:

roots = 1+/- sqrt(71), so

x^2 - 2*x -35 = (x - 1 - sqrt(71))*(x - 1 + sqrt(71))

You have to try values less, in between or greater than the roots. GOing straight to the point,

(-infinity, 1 - sqrt(71) ) And ( 1 +  sqrt(71), infinity)


ACCESS MORE